Visionary Leadership and Teacher Competence in Enhancing Teacher Performance: The Mediating Role of Knowledge Sharing - Djoko Soelistya; Indah Puji Lestari; Moh. Agung Surianto (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to analyze the influence of visionary leadership and teacher competence on teacher performance with knowledge sharing as a mediating variable at SMA Negeri 1 Parengan, Tuban Regency. Design/methodology/approach – This study used a quantitative approach with an explanatory design. Data were collected through questionnaires to 38 teachers with a saturated sampling technique. Data analysis used the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). Finding/Results – The results showed that visionary leadership had a positive and significant effect on knowledge sharing and teacher performance. Teacher competence was also proven to have a positive and significant effect on knowledge sharing and teacher performance. In addition, knowledge sharing had a positive and significant effect on teacher performance. The results of the mediation test showed that knowledge sharing acted as a partial mediating variable in the relationship between visionary leadership and teacher competence on teacher performance. These findings indicate that improving teacher performance is not only influenced by the principal's leadership and individual competence, but also by the culture of knowledge sharing that develops in the school environment. Originality/Value – Therefore, strengthening visionary leadership and developing teacher competence needs to be accompanied by the creation of an effective knowledge sharing culture to optimally improve teacher performance.